Analisis Pendapatan dan Rentabilitas UMKM Keripik Singkong di Desa Bukit Peninjauan I Kecamatan Sukaraja Kabupaten Seluma (Studi Kasus PT. Rizky Jaya Sampurna) - Sari, Nur Phita; Feni, Rita; Efrita, Edi; Marwan, Edy; Mulyadi, Maheran (Jurnal MeA (Media Agribisnis), 2024)
Casava crackers are commonly produced snack by SMEs, one of which is PT. Rizky Jaya Sampurna. This study aims to analyze revenue and rentability of casa crackers at PT. Rizky Jaya Sampurna. The data used in this study is primary and secondary data. Primary data obtained by using interview through questionnaire to the owners of PT. Rizky Jaya Sampurna while secondary data obtained from relevant bodies. The data collected in this study comprised investment cost, fixed cost, variable cost, production, and price. Data analysis consisted of cost analysis, revenue, R/C ratio, B/C ratio, profile rate, pay back period and rentability. The result shows that total cost is Rp31.535.019,44, revenue is Rp12.984.980,56 per month, R/C ratio is 1,41, B/C ratio is 0,41, profile rate is 41,2%, payback period is 6 years 6 month and 27 days and rentability is 14,6%. The study concluded that casava crackers SMEs by PT. Rizky Jaya Sampurna is not feasible for long term production based on below one B/C ratio, but the business is already profitable and efficient.